0149 Reliability of Heart Rate Variability during Stable and Disrupted Polysomnographic Sleep. (25th May 2022) - Kerkering, Emma; Greenlund, Ian; Bigalke, Jeremy; Migliaccio, Gianna; Tikkanen, Anne; Nicevski, Jennifer; Carter, Jason
Abstract: Introduction: Heart rate variability (HRV) is a common metric to estimate autonomic activity during sleep. Frequency-domain HRV is quantified as low (LF) and high (HF) frequency, whereas HRV time-domain indices include root mean square of successive R-R interval differences (RMSSD), and percentage of successive R-R intervals differing by more than 50ms (pNN50). Despite high HRV use during sleep, it is unknown whether sleep disturbance changes overall reliability of frequency- and time-domain HRV. The purpose of this present study was to determine whether HRV was reliable across arousal-free and arousal-containing periods of sleep. Methods: Twenty-seven participants (11 male, 16 female, 26±1 years, 27±1 kg/m2) were given an 8-hour sleep opportunity, equipped with continuous two-lead electrocardiography (ECG) and overnight polysomnography (PSG). The ECG recordings were analyzed via fast-Fourier transformation for frequency-domain HRV in a custom software as LF (0.04-0.15 Hz) and HF (0.15-0.4 Hz) HRV. Time-domain HRV was quantified as RMSSD and pNN50. Two separate stable sleep periods (range, 5-10min) absent of arousals were recorded, along with two separate disrupted periods of sleep with at least one arousal were selected in stage II sleep (N2), slow wave sleep (SWS), and rapid eye movement (REM) sleep. LF and HF HRV was log10 transformed due to non-normal distribution. Statistical analysis included intraclass correlations (ICC) of HRV across the four stable and disrupted periods of sleep, with separate ICC analyses across sleep stages (α = 0.05). Results: Time-domain measures (RRI, RMSSD, pNN50) were reliable across arousal-free and arousal-containing sleep cycles, for all three stages (ICC>0.9, p<0.05). HF HRV exhibited similar reliability patterns across N2 sleep (ICC=0.960, p<0.001), SWS (ICC=0.955, p<0.001), and REM sleep (ICC=0.924, p<0.001). LF HRV was reliable in two stages of stable and disrupted sleep in N2 (ICC=0.903, p<0.001), REM (ICC=0.907, p<0.001) sleep, and trending in SWS (ICC=0.616, p=0.089) sleep. Conclusion: Time- and frequency-domain HRV were reliable between stable sleep with and without cortical arousals, with the exception of LF HRV during SWS. Taken together, HRV may provide a reliable, indirect index of autonomic activity across stable and disrupted sleep. Support (If Any): Support: Support is provided by the National Institutes of Health (AA-024892; U54GM115371; P20GM103474).